Application of zeolites for biological treatment processes of solid wastes and wastewaters – A review. (April 2020) - Montalvo, S.; Huiliñir, C.; Borja, R.; Sánchez, E.; Herrmann, C.
Graphical abstract: Highlights: Many evidences are showed about favorable uses of zeolite in biological processes. In aerobic processes zeolite is used as ion-exchanger and biomass carrier. In anaerobic digestion, zeolite is used to remove ammonia and biomass carrier. In composting, zeolite is used to retain ammonia and to remove heavy metals. Zeolite has been used at industrial scale mainly in nitrogen removal. Abstract: This review reports the use of zeolites in biological processes such as anaerobic digestion, nitrification, denitrification and composting, review that has not been proposed yet. It was found that aerobic processes (activated sludge, nitrification, Anammox) use zeolites as ion-exchanger and biomass carriers in order to improve the seattlebility, the biomass growth on zeolite surface and the phosphorous removal. In the case of anaerobic digestion and composting, zeolites are mainly used with the aim of retaining inhibitors such as ammonia and heavy metals through ion-exchange. The inclusion of zeolite effect on mathematical models applied in biological processes is still an area that should be improved, including also the life cycle analysis of the processes that include zeolites. At the same time, the application of zeolites at industrial or full-scale is still very scarce in anaerobic digestion, being more common in nitrogen removal processes.